Effect of fibrinogen degradation products on platelet aggregation - Wilson, Patricia A. (1968)
The digestion of fibrinogen with various concentrations of trypsin results in the formation of a variety of degradation products. Degradation products formed in this way have been purified by DEAE cellulose column chromatography and their effects on platelet aggregation investigated. Two methods have been used to study platelet aggregation: a turbidimetric method which assesses platelet aggregation by the ability of adenosine diphosphate (ADP) to clump platelets and a method which assesses platelet adhesiveness by their ability to adhere to glass and to each other (modified Hellem technique, 1960). Three breakdown products produced by trypsin-digested fibrinogen were studied and all showed `antithrombin' activity: two inhibited platelet aggregation, but one accelerated aggregation in both systems. Another product prepared by digestion of fibrinogen with urokinase-activated plasminogen has been shown to possess the ability to enhance ADP-induced platelet aggregation.